2018
DOI: 10.1177/1524838018772293
|View full text |Cite
|
Sign up to set email alerts
|

Global Posttrauma Symptoms: A Systematic Review of Qualitative Literature

Abstract: Exposure to potentially traumatic events is a global health problem, especially in low- and middle-income countries. Assessments for symptoms resulting from trauma exposure rely heavily on the Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5) criteria for post-traumatic stress disorder (PTSD), which may not be relevant in all regions of the globe. We examined posttrauma symptoms that were not limited to Western constructs of mental health (i.e., PTSD). In a systematic review, we sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 54 publications
(63 reference statements)
3
18
1
2
Order By: Relevance
“…However, contrary to some existing work (Michalopoulos et al, 2015;Neugebauer et al, 2009;Rasmussen et al, 2014;Smith Fawzi et al, 1997), we found that both reexperiencing and avoidance symptoms were common. Lastly, we did not find either of the following symptoms described in previous work: persistent inability to experience positive emotions and detachment from others (Michalopoulos et al, 2020). It is possible that "holding everything to myself" was a local expression of the detachment symptom, although it could also be mistrust of others (i.e., persistent negative beliefs about others).…”
Section: Discussioncontrasting
confidence: 79%
“…However, contrary to some existing work (Michalopoulos et al, 2015;Neugebauer et al, 2009;Rasmussen et al, 2014;Smith Fawzi et al, 1997), we found that both reexperiencing and avoidance symptoms were common. Lastly, we did not find either of the following symptoms described in previous work: persistent inability to experience positive emotions and detachment from others (Michalopoulos et al, 2020). It is possible that "holding everything to myself" was a local expression of the detachment symptom, although it could also be mistrust of others (i.e., persistent negative beliefs about others).…”
Section: Discussioncontrasting
confidence: 79%
“…However, the lack of reliable and valid instruments used in the populations studied is a major limitation for both research and practice. In a 2018 review of qualitative studies examining post-trauma symptoms across cultural contexts, most study participants reported symptoms consistent with Western diagnostic criteria but also reported a number of symptoms not captured in those diagnostic classifications [107], supporting the need for local contextualization of measures. Measures that are not locally contextualized and valid may result in substantial under-or overreporting of trauma exposure and PTSD symptoms.…”
Section: Limitationsmentioning
confidence: 99%
“…(1) Posttraumatic stress symptoms structure and function may be affected by unique socio-cultural factors and context that shape understanding, attribution as well as responding to traumatic events (e.g., political persecution secondary to ethno-linguistic group status, torture, etc.) (Hinton & Lewis‐Fernández, 2011; Kelley, Weathers, McDevitt‐Murphy, Eakin, & Flood, 2009; Michalopoulos et al., 2020). For example, in the studied E. African groups, sexual assault is highly socially stigmatized and likely to lead community ostracism; likewise, a number of traumatic events were experienced as a function of actions of the ruling political regime attacking specific political or ethnic group(s) (Badri, Alia, Van den Borne, & Crutzen, 2013; Badri, et al., 2012; Plaut, 2017; Rasmussen, Katoni, Keller, & Wilkinson, 2011; Van Reisen & Mawere, 2017)) (see Supplemental Material for additional information).…”
Section: Discussionmentioning
confidence: 99%
“…Results are thus circumscribed to this pool of symptoms/nodes. In addition or alternatively, it may be promising to model symptoms framed in local and socio-culturally-specific concepts or idioms reflective of “symptoms” (Michalopoulos et al., 2020; Rasmussen et al., 2014). Fourth, data are cross-sectional data limiting inferences regarding directional or causal functional associations between symptoms.…”
Section: Limitationsmentioning
confidence: 99%